Biologia comparada de Trialeurodes vaporariorum (West.) (Hemiptera - Homoptera: Aleyrodidae) em soja e cinco cultivares de feijão - Campos, Ostenildo R. [UNESP]; Crocomo, Wilson B. [UNESP]; Labinas, Adriana M. (Springer Nature, 2003)
With the development of greenhouse grown crops, the whitefly Trialeurodes vaporariorum (West.) has become an important pest. Aiming at verifying the effect of host on the development of this species, the biology of the whitefly was studied on bean (Phaseolus vulgaris L.) cultivars IAC-Carioca Pyatã, IAPAR-57, Jalo Precoce, IAC-Bico de Ouro, IAC-Maravilha and on soybean (Glycine max L.) cultivar Cristalina. The study was conducted at the Laboratório de Entomologia Agrícola - FCA-UNESP, at 25 ± 3°C temperature, 80 ± 10% RH and 14h photophase. The biological parameters assessed were duration, viability and number of nymphal instars; male and female longevity, oviposition period, number of eggs per female and sex ratio; egg viability and incubation period and the life cycle duration. Based on data obtained, fertility life tables were constructed to allow a comparative analysis of the effect of cultivars on the biological development and consequent population growth of this species. The bean cultivars IAC-Maravilha and Jalo Precoce negatively influenced T. vaporariorum development, whereas, the other bean cultivars studied, as well as the soybean cultivar Cristalina, provided good conditions for development of this pest.
Comparative biology of the whitefly Trialeurodes vaporariorum (West.) (Hemiptera - Homoptera: Aleyrodidae) on soybean and bean cultivars
Keywords: Insect/plant relationship; Insecta; Life table; Whitefly; Aleyrodidae; Glycine max; Hemiptera; Phaseolus vulgaris; Trialeurodes vaporariorum